Kejadian Hipertensi dan Kesehatan Ginjal di Desa Marada Mundi Kecamatan Kambata Mapambuhang Kabupaten Sumba Timur - Treesia Sujana; Rosiana Eva Rayanti; Tedy Christopel Keluanan (Jurnal Keperawatan Muhammadiyah, 2019)
Background: Hypertension and kidney health problems often occur in various parts of the world and Indonesia especially in Sumba Hypertension can influence the condition of kidney patients. Objective: to identify hypertension and kidney health status of the elderly. Method: quantitative with purposive sampling among 45 respondents of elderly who have hypertension in Marada Mundi village, Kambata Mapambuhang East Sumba districts, East Nusa Tenggara Province. The purposive sampling criteria are respondents who are 50 years or older and residents of Marada Mundi Village. The research analysis uses the calculation of mean, percent, and standard deviation. Research instruments are sphygmomanometer, urine dipstick, urine container, and form intake output questionnaires. Results: Majority of the respondents have stage 1 hypertension (42,2%), have normal pH (91,1 %), proteinuria (57.8%), but there is no glucose found in the urine.  Respondents with less fluid are 37 respondents, 7 respondents have excessive fluid, while 1 respondent has fluid balance. Mean of fluid intake is 3116.00 ml and fluid output is 3326.33 ml. All respondents meet the fluid need even beyond the body need based on the weight. Conclusion: the proportion of respondents who have hypertension is 97% with normal pH levels (91.1%) and proteinuria (58.7%). Although the respondent’s fluid balance is less, actually they meet the actual needs of the fluid more than the body’s ideal needs.